2020
DOI: 10.3390/ijerph17030996
|View full text |Cite
|
Sign up to set email alerts
|

Poor Sleep Is a Risk Factor for Low-Back Pain among Healthcare Workers: Prospective Cohort Study

Abstract: This study aimed to investigate the association between poor sleep and risk of low-back pain (LBP) in healthcare workers. Using a prospective cohort design with 1-year follow-up, a total of 1955 healthcare workers (60% nurses) from 389 departments at 19 hospitals responded to questionnaires containing items related to lifestyle, health, and working environment. Associations between sleep scores (0–100) at baseline and LBP intensity (0–10) at follow-up were modelled using cumulative logistic regression accounti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 40 publications
1
20
0
3
Order By: Relevance
“…Prior to this analysis, we have previously published associations between lifestyle factors and the outcome of poor sleep and pain (8,29), as well as data on the prospective association between patient transfers and back injury (30).…”
Section: Methodsmentioning
confidence: 99%
“…Prior to this analysis, we have previously published associations between lifestyle factors and the outcome of poor sleep and pain (8,29), as well as data on the prospective association between patient transfers and back injury (30).…”
Section: Methodsmentioning
confidence: 99%
“…Various studies have demonstrated that brief rest in all populaces, is major cause for fatigue, high blood pressure, insulin resistance, cardio and vascular disease. 14 Sleep disorder is a rising public health concern worldwide. It can be influenced by environmental, cultural and behavioural factors and is estimated to have a prevalence of 10 to 48%.…”
Section: Introductionmentioning
confidence: 99%
“…Taking into consideration the high incidence of musculoskeletal conditions in occupational health groups. 14 Research investigating the effect of sleep disruption on low back pain severity have shown a substantial correlation between sleep quality and intensity of pain, exhaustion, subsequent-day function and psychological distress. Individuals with low back pain who have sleep issues and more extreme pain have also been reported to be at higher risk of being hospitalized for low back pain than people with good sleep quality.…”
Section: Introductionmentioning
confidence: 99%
“…The survey used in the present study was partially based on the 2018 round of the Danish Work Environment Cohort Study (DWECS) - from which we have previously reported associations between pain, stress and sleep among healthcare workers [ 35 – 37 ] - and included questions concerning lifestyle-, health- and factors related to the work environment. While the entire questionnaire exists only in Danish, the questions used in this study have been translated and included in this section; containing questions specific to the work environment of healthcare workers.…”
Section: Methodsmentioning
confidence: 99%